A Comparison Approach in Corruption Eradication: An Empirical Examination - Mispansyah Mispansyah (Faculty of Law, Hasanuddin University, 2018)
Corruption in Indonesia is increasingly structured and systemic. Worse yet, the corruption was fertile in sub-law enforcement agencies. This paper analyzes why corruption is so systemic in the legal system in Indonesia and how solution of Islam in eradicating corruption. This research was a normative-legal research. The results indicate that corruption occurred systemically in Indonesia due to secularization and capitalization in understanding the living system as embraced by the Republic of Indonesia, which resulted in bad law system both the substance, structure and legal culture, and bad people). The solution of Sharia Islam to eradicate corruption by creating a devotion of community (law awareness) based on religious values. In addition, with a decent salary system, appropriate penalties, the implementation of reverse evidence system and the exemplary leadership, corruption problems can be overcome and a clean government can be realized.